East
CentricArch
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
RosalindManire
Feb 5, 2018, 7:00:20 AM
14
What is x2 -6x-23=0 using square roots
+1
(
1
) Answers
KayIseman
Feb 5, 2018, 4:34:07 PM
-4x - 23 = 0 +23 = +23 -4x = 23 -4. -4x Answer:5.75
Add answer
Sign in
Sign up
Related Questions
What is x2 -6x-23=0 using square roots
solve 3x^2-27=0 using square roots
Using the product property of square roots what is the square root of 28 and 150
if the quadratic formula is used to find the roots of the equation x^2-6x-19=0, what is the corre...
Solve x2 − 8x + 5 = 0 using the completing-the-square method.
Solve x2 + 12x + 6 = 0 using the completing-the-square method.
what are the real roots of x2-7×+10=0
What is the general form of the equation of the given circle with center A? CenterA:(-3,12) Radiu...
Solve x2 + 6x = 7 by completing the square. What is the solution set of the equation?
Solve the quadratic equation by completing the square. x2 + 6x - 5 = 0